KONSEP MUTU DAN MUTU PENDIDIKAN: PENERAPAN KONSEP PANCA CINTA DALAM KURIKULUM BERBASIS CINTA DI SMA NEGERI 1 KAYUAGUNG - Siti Rahmatullisa; Ahmad Zainuri; Muslim Gani Yasir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to conceptually analyze the relationship between Human Resource Management (HRM) practices and teacher performance, with work engagement as a mediating variable. The study employed a qualitative approach with library research. Data were obtained through literature analysis over the past five years (2020–2025) from reputable international journals and accredited national journals. The synthesis results indicate that strategic HRM practices such as continuous training, competency-based performance evaluation systems, fair compensation, and transformational leadership significantly influence work engagement. Furthermore, work engagement was shown to be the primary psychological mechanism mediating the relationship between HRM practices and teacher performance improvement. These findings reinforce Strategic Human Resource Management theory and research findings in The International Journal of Human Resource Management (2022) and Human Resource Management Journal (2021). This study concludes that optimizing strategic and humanistic-based HRM systems is key to continuously improving the quality of education.